Soil improvement by trees in sub-Saharan Africa - Buresh, R.J.; Tian, G. (Springer, 1997)
Trees can influence both the supply and availability of nutrients in the soil. Trees increase the supply of nutrients within the rooting zone of crops through (1) input of N by biological N2 fixation, (2) retrieval of nutrients from below the rooting zone of crops and (3) reduction in nutrient losses from processes such as leaching and erosion. Trees can increase the availability of nutrients through increased release of nutrients from soil organic matter (SOM) and recycled organic residues. Roots of trees frequently extend beyond the rooting depth of crops. Research on a Kandiudalfic Eutrudox in western Kenya showed that fast-growing trees with high N demand (Calliandra calothyrsus, Sesbania sesban and Eucalyptus grandis) took up subsoil nitrate that had accumulated below the rooting depth of annual crops. Sesbania sesban was also more effective than a natural grass fallow in extracting subsoil water, suggesting less leaching loss of nutrients under S. sesban than under natural uncultivated fallows. Nutrient release from SOM is normally more dependent on the portion of the SOM in biologically active fractions than on total quantity of SOM. Trees can increase inorganic soil N, N mineralization and amount of N in light fraction SOM. Among six tree fallows of 2- and 3-year duration on an Ustic Rhodustalf in Zambia, inorganic N and N mineralization were higher for the two tree species with lowest (lignin + polyphenol)-to-N ratio (mean = 11) in leaf litter than for the two tree species with highest ratio (mean = 20) in leaf litter. Trees can also restore soil fauna, which are important for SOM and plant residue decomposition. Some agroforestry trees have potential to provide N in quantities sufficient to support moderate crop yields through (i) N inputs from biological N2 fixation and retrieval of nitrate from deep soil layers and (ii) cycling of N from plant residues and manures. The cycling of P from organic materials is normally insufficient to meet the P requirements of crops. Sustained crop production with agroforestry on P-deficient soils will typically require external P inputs.